From Charity to Development: Repositioning Waqf in Islamic Social Finance - Adamu Abubakar Muhammad; Adam Muhammad Ardo; Maryam Adam; Bala Babangida (AL-IMAM: Journal on Islamic Studies, Civilization and Learning Societies, 2026)
Within the larger context of Islamic social finance, this research explores how waqf has evolved from a conventional charitable organization to a useful tool for long-term socioeconomic development. In Muslim societies throughout history, waqf has been essential in promoting communal welfare, healthcare, education, and religious institutions. However, weak governance structures, insufficient legal and regulatory frameworks, poor asset management, and a lack of strategic alignment with national and community development goals have limited its effectiveness in many modern contexts. Waqf is therefore frequently limited to temporary humanitarian endeavors rather than being utilized as a long-term development organization. This research investigates the evolving role of waqf within Islamic social finance using a qualitative research technique. It draws on an extensive survey of scholarly literature, policy documents, chosen case studies, and insights from expert interviews. The analysis finds important institutional, ethical, and practical constraints that impede waqf's developmental potential, such as governance flaws, inadequate transparency, poor public awareness, and fragmented cooperation with other Islamic social finance mechanisms like zakat. The findings show that waqf has considerable untapped potential to contribute to long-term human development when repositioned within a comprehensive development framework. Institutional reforms, professional management practices, accountability systems, and policy integration appear to be significant variables for improving its efficacy. The research suggests that integrating waqf with maq??id al-shar??ah objectives and current development concerns can reposition it as a sustainable funding mechanism alongside other Islamic finance instruments. The research concludes with practical policy proposals aimed at strengthening waqf governance, institutional capacity, and strategic relevance, thus increasing its contribution to long-term social and economic growth in Muslim nations.